Clinical and Epidemiological Characteristics of Mpox in HIV-Infected and Uninfected Men Who Have Sex with Men: A Retrospective Study in Lisbon - Diogo de Sousa; Yuliya Volovetska; Daniel Nunes; Carlos Lemos; João Borges-Costa; Paulo Filipe (Viruses, 2024)
The resurgence of Mpox, predominantly among men who have sex with men (MSM), has prompted an analysis of its clinical manifestations and epidemiological patterns, particularly in individuals living with human immunodeficiency virus (HIV). This retrospective study aims to delineate and compare the clinical presentations and epidemiological characteristics of Mpox among HIV-positive and HIV-negative individuals. A total of 58 confirmed Mpox cases from a dermatology department in Lisbon were analyzed, focusing on mucocutaneous manifestations, systemic symptoms, and laboratory parameters. Our findings indicate no significant difference in disease severity and presentation between HIV-positive and HIV-negative groups, suggesting that HIV status may not be a determinant of Mpox severity, but rather an indicator of increased sexual risk behaviors, a recognized risk factor for Mpox transmission.